Case Report: Pulmonary Vein Isolation as a Tailored Treatment for Recurrent Ventricular Tachycardia During Hemodialysis in a Patient With Right Coronary Artery Chronic Total Occlusion - Cojocaru, Cosmin; Pupăză, Adelina; Iorgulescu, Corneliu; Onciul, Sebastian; Câlmâc, Lucian; Vătăşescu, Radu (Frontiers in Cardiovascular Medicine, 2022)
Background: Catheter ablation of ventricular substrate can reduce ventricular tachycardia (VT) recurrence and mortality in electrical storm (ES). However, identification and specific treatment of plausible triggers is mandatory and may lead to resolution of ES. Objective: This case presentation seeks to exemplify how pulmonary vein isolation (PVI) may represent a tailored-treatment of ES in cases of ventricular substrate which only becomes arrhythmogenic during high-rate episodes of paroxysmal atrial fibrillation (PAF). Results: A 54-year-old male with a history of inferior myocardial infarction (MI) and long-term haemodialysis was referred for repetitive implantable cardioverter defibrillator (ICD) shocks for apparently scar-related monomorphic VT episodes preceded by PAF initiation strictly during haemodialysis. He had recently undergone ICD implantation for similar episodes of ES preceded by rapid-ventricular response (RVR) PAF during haemodialysis. The patient had no other history of VTs. EKG changes occurred exclusively during PAF and suggested functional myocardial ischemia. Coronary angiography demonstrated isolated right coronary artery (RCA) chronic total occlusion (CTO). Cardiac magnetic resonance demonstrated RCA-territory residual myocardial viability and mild LV systolic dysfunction. Surgical revascularization was not feasible due to a history of bilateral above-the-knee post-traumatic amputation and severe calcification of internal mammary (IMA) and radial arteries. Subsequent CTO-percutaneous coronary intervention attempt was unsuccessful. The difficulty of assessing LV-substrate ablation end-points due to the “functional” character of substrate which only became arrhythmogenic during haemodialysis-related PAF was considered. Consequently, PVI was performed rather than VT/VF substrate ablation. 12 months after PVI the patient remains free of PAF and VT/VF despite chronic haemodialysis sessions. Conclusion: ES episodes can be triggered by situational factors such as RVR-PAF and functional ischaemia during haemodialysis in CTO patients with otherwise no episodes of VT. Tailored treatment of such factors may lead to long-term VT freedom.